1999
DOI: 10.1002/(sici)1521-3927(19990901)20:9<487::aid-marc487>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of ethylene with new diimine complexes of late transition metals

Abstract: SUMMARY: Three pyridylimine based complexes of Ni II and Co II were reacted with methylaluminoxane (MAO) and tested as catalysts in ethylene polymerization. The two nickel catalysts produced mainly methyl branched polymers with good to moderate activity, while the cobalt compound showed only marginal activity. Reaction conditions strongly affect the polymer properties, such as molecular weight, melting temperature, degree of branching, and chain end unsaturation type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 0 publications
5
40
0
Order By: Relevance
“…In line with the observations taken for other iminopyridyl late‐transition‐metal precatalysts such as 9‐aryliminocyclo[ b ]heptapyridyl nickel chlorides, the catalytic activity of Ni1 /MAO sharply decreases as the temperature is elevated from 20 °C to 70 °C; simultaneously the polyethylene molecular weight also decreases (entries 3, 6–11, Table and Fig. ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In line with the observations taken for other iminopyridyl late‐transition‐metal precatalysts such as 9‐aryliminocyclo[ b ]heptapyridyl nickel chlorides, the catalytic activity of Ni1 /MAO sharply decreases as the temperature is elevated from 20 °C to 70 °C; simultaneously the polyethylene molecular weight also decreases (entries 3, 6–11, Table and Fig. ).…”
Section: Resultssupporting
confidence: 84%
“…a Various ligand architectures have been developed to support the nickel center; these include the bidentate N^N, N^P, N^O, P^O, and tridentate N^N^N, N^N^O, N^P^N systems. Among the N,N ‐bidentate ligands, α‐diimines a, ( A , Scheme ) and various 2‐iminopyridine derivatives a, ( B , Scheme ) have been the most popular; the former can easily be synthesized from either simple diketones a, or acenaphthylene‐1,2‐dione and its analogues . a, The nickel complexes bearing these ligands turned out to be the precursors of very active catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, bidentate ligands of the N^N, N^O, N^P, P^O chelating modes can also be developed to attain the same goal. The 2‐iminopyridylnickel complexes have recently drawn significant attention . For example, it was found that the precatalysts based on 5,6,7‐trihydroquinolin‐8‐one derivatives promoted ethylene polymerization, whilst the oligomerization was observed in the case of nickel precatalysts with the 2‐substituted (Cl/Ph/Me/ i ‐Pr) 8‐arylimino‐5,6,7‐trihydroquinolines .…”
Section: Introductionmentioning
confidence: 99%
“…Complexes can be isolated as mononuclear species or, depending on both the metal halides and the degree of substitution of the pyridine ring, as centrosymmetric dinuclear molecules. [8][9][10][11] By simple modifications of the iminopyridyl architecture, the polymerization and/or oligomerization activities of the metal complexes can be tuned. All these merits make this class of complexes advantageous over other types of metal catalyst, such as metallocenes or geometry constrained species [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%